2016
DOI: 10.1155/2016/7536108
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Knitted Fabric Porosity and Light Permeability

Abstract: The present paper attempts to investigate the relationship between fabric porosity and light permeability of the knitted structures, namely, rib 1 × 1, rib 2 × 1, single jersey, and plain structure. The rationale is that pores (in a fabric) would allow light to pass through but at the same time provide a quantitative assessment of the UV light permeability of the knitted fabrics, an indication of the protective capacity of the fabrics against UV radiation. The porosity and corresponding light permeability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Objective determination of the porosity in the textile fabrics is gaining importance; the technique of image analysis is being used to determine the porosity of woven and knitted fabrics (Angelova, 2012; Imrith et al , 2016a, 2016b). The researchers are also exploring the relationship of porosity with air permeability (Çay et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Objective determination of the porosity in the textile fabrics is gaining importance; the technique of image analysis is being used to determine the porosity of woven and knitted fabrics (Angelova, 2012; Imrith et al , 2016a, 2016b). The researchers are also exploring the relationship of porosity with air permeability (Çay et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that increase in yarn fineness and more open structure, yarns with lower hairiness of the knitted fabric, higher porosity and lower compactness improve the air permeability, and the tightness factor correlates more with air permeability than knitted fabric thickness (Bhattacharya and Ajmeri, 2013). Imrith et al (2016)…”
Section: Introductionmentioning
confidence: 99%
“…Literature review reveals that the knitted fabrics are usually tested for the air permeability which depends on variety of factors, such as fabric porosity (Tou, 2005;Bhattacharya and Ajmeri, 2013;Imrith et al, 2016;Jordeva et al, 2017;Havlová and Špánková, 2017), course count and yarn number (Tou, 2005), loop length (Chidambaram et al, 2011), loop density and knit type (Dehkordi et al, 2017), thickness, tightness, yarn fineness and compactness (Bhattacharya and Ajmeri, 2013), raw material content ( Jordeva et al, 2017), etc. It was also considered that air will primarily flow through the inter-yarn pores in knitted fabrics; only in the case of highly dense fabrics may be considered that the part of the air may pass through the surface layers of the yarn (Havlová and Špánková, 2017).…”
mentioning
confidence: 99%